The impact of urban green space on the health of middle-aged and older adults - Li, Qiangyi; Liu, Yangqing; Yang, Lan; Ge, Jiexiao; Chang, Xiaona; Zhang, Xiaohui (Frontiers in Public Health, 2023)
Abstract Introduction: Urban green space is one of the most closely related ecosystem services to residents' lives, and it can be regarded as a preventive public health measure. Residents living in parks and other green environments can help improve their physical and mental health, reduce stress and even prevent crime and violence. Therefore, based on the actual situation in China, this paper analyzes the relationship between urban green space and the health of middle-aged and elderly people and its mechanisms. Methods: This study used multiple linear regression, based the data from the China Health and Retirement Longitudinal Study (CHARLS) in 2013, 2015, and 2018, to explore the relationship between urban green space and the health of middle-aged and elderly people. At the same time, group regression was conducted to identify the heterogeneity of health effects of urban green space. Results: The research shows that the increase of urban green space areas can significantly improve the health status of middle-aged and elderly people. After a series of robustness tests, the results are still valid. In addition, the health effects of urban green space are different because of gender, age, education level, marital status and residence. Further research found that reducing hot weather and optimizing air quality are the potential mechanisms of urban green space affecting the health of middle-aged and elderly people, providing new evidence for the causal mechanism between urban green space and the health of middle-aged and elderly people. Discussion: This study expanded the research scope of the impact of urban green space on the health of middle-aged and elderly people, covering a representative sample in China. The results show that urban green space has an important impact on the health of middle-aged and elderly people. Policy suggestions are made to help cities optimize the landscape and residents to enjoy ecological.